Store image: proposition of scale to the retail pharmaceutical segment - Souza, Ronaldo Barbosa de (2011)
The retail pharmaceutical market, which has been gradually taking up more space in the large domestic retail segment, is characterized by a high number of sales points and an intensive market competition, developed by the big chains and small pharmacies. The latter are the majority in the universe of 59,000 pharmacies in Brazil. The former strategy of considering location as the main source of competitive advantage has been eroded in these times, and issues of store image emerge with a real possibility of differentiation to increasingly demanding customers. The aim of this study is to evaluate the impact of store image on a pharmacy. The work was developed using the clients of pharmacies in a major city in the State of Minas Gerais as the universe. Data were provided by the clients of a network of pharmacies in that municipality and, after statistical treatment, the sample data showed the importance of store image to the pharmacies. Of a total of 30 variables associated with store image, a set of nine attributes was identified to conceptually approximate the components of the marketing mix.